Chapter Monarchia, signori e feudi nei regni di Sicilia e Napoli (secoli XIII-XV) - d'Arcangelo, Potito (Reti Medievali E-Book, 2023)
The essay looks into the troubled relationship between sovereign power and feudal power in the Kingdoms of Naples and Sicily after the Vespro. Moving from the analysis of the European and Mediterranean political space in which both reigns were embedded, it brings out the repercussions of the political and military history on the evolution of Southern seigneuries, the role of the papacy, the placement of seigneuries and fiefs within the monarchic state.